Assessment of Ondansetron-Associated Hypokalemia in Pediatric Oncology Patients. (19th September 2012) - Fiedrich, Elsa; Sabhaney, Vikram; Lui, Justin; Pinsk, Maury
Abstract : Objectives . Ondansetron is a 5-hydroxytryptamine (5-HT3, serotonin) receptor antagonist used as antiemetic prophylaxis preceding chemotherapy administration. Hypokalemia is a rare complication of ondansetron, which may be underreported due to confounding emesis and chemotherapy-induced tubulopathy. We performed a prospective cohort study to determine if ondansetron caused significant hypokalemia independently as a result of renal potassium wasting. Methods . Twelve patients were recruited, with ten completing the study. Blood and urine samples were collected before and after ondansetron administration in patients admitted for intravenous (IV) hydration and chemotherapy. Dietary histories and IV records were analyzed to calculate sodium and potassium balances. Results . We observed an expected drop in urine osmolality, an increase in urine sodium, but no statistically significant change in sodium or potassium balance before and after ondansetron. Conclusion . Ondansetron does not cause significant potassium wasting in appropriately hydrated and nutritionally replete patients. Careful monitoring of serum potassium is recommended in patients with chronic nutritional or volume status deficiencies receiving this medication.